Water politics and development cooperation : local power plays and global governance - Neubert, Susanne (Springer, 2017)
The importance of the political sphere for understanding and solving water sector problems is the basic rationale of this book, which is the outcome of the Fifth Dialogues on Water, organised at the German Development Institute, Bonn. These dialogues, unlike earlier ones, focused on the political processes of policy formulation and the strategic behaviour of the actors involved. Specific attention is devoted to implications for development cooperation.